2006
DOI: 10.1002/mrc.1787
|View full text |Cite
|
Sign up to set email alerts
|

Stability constants: comparative study of fitting methods. Determination of second‐order complexation constants by23Na and7Li NMR chemical shift titration

Abstract: NMR chemical shift titration has been widely used as a method for the determination of stability constants. Systems involving metal-ligand complexation have been investigated using a number of methodologies. There are significant differences in the values reported for stability constants obtained by different experimental methods, such as calorimetry and ion selective electrode (ISE) titrations; nor has NMR chemical shift titration always yielded consistent results. Different researchers have obtained differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…It is common practice in the literature to report log K values for stability constants. As we pointed out in a previous study, [16] since log is not a linear function, symmetrical error bars on log K imply unsymmetrical errors in the value of K. Since we have reported values for K from other studies, we follow our previous method of reporting K as the antilog of these log K values and including the unsymmetrical error for these cases. K values from this study were reported directly along with their errors from the regression.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…It is common practice in the literature to report log K values for stability constants. As we pointed out in a previous study, [16] since log is not a linear function, symmetrical error bars on log K imply unsymmetrical errors in the value of K. Since we have reported values for K from other studies, we follow our previous method of reporting K as the antilog of these log K values and including the unsymmetrical error for these cases. K values from this study were reported directly along with their errors from the regression.…”
Section: Discussionmentioning
confidence: 91%
“…The notation used here follows closely that of Ref. [16]. It is common practice in the literature to report log K values for stability constants.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations